Analysis of the Functioning Practice of the Insurance Market of the Republic of Uzbekistan - Zikriyaev Zokir Mamirovich; Nematullaeva Zarina Zafar kizi; Salomova Visola Zafar kizi (Genius Journals, 2023)
At the moment, the insurance market of Uzbekistan continues to develop and attract the attention of foreign investors. This article analyses the insurance market of the Republic of Uzbekistan, its development trend, comparisons with previous years.
Keywords: Insurance; insurance market; insurance policies; life insurance